Influence of Sports Marketing Strategies in the Promotion of Organization Products and Services in Ilorin Metropolis - Issa Yaqub Ajeigbe (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
Sport marketing remain an important aspect of global sports innovation as it is relevant to the growth of business as well as its survival. It is further prescribed as a means by which company or an organization communicate their services in a sport-oriented context. Sports marketing has been developed to promote sports events and teams as well as promotion of other products and services to consumers. Descriptive survey design was used in this study. The population comprised the sport marketers and organizations that produce and sell sport products and services to consumers totaling 54 and no sample was selected as all the marketers and organization staff were used as sampled for the study. Structured questionnaire designed in a four point likert rating scale which was validated by experts in sports marketing and tested for reliability with coefficient result of 0.82 was used to elicit data from the respondents. Two research questions and two research hypotheses were formulated for the study. The two research questions were analysed using frequency, percentage and means score while the hypotheses were tested using independent T-test at 0.05 level of significant and funding reveals that there was no significant difference in the sport marketer perception of the influence of sport marketing strategy on the promotion of organization products as well as to produce valued products based on gender,. Among the recommendations, suggested include: organization must strengthen btheir marketing strategies in order to promote their products among others Keywords: Sports marketing, strategies, and promotion of organization products and services